Rasio Protein Nabati dengan Protein Hewani dalam Kaitannya dengan Marker Gangguan Ginjal: Tinjauan Sistematis Studi Kohort: Rasio Protein Nabati dengan Protein Hewani dalam Kaitannya dengan Marker Gangguan Ginjal: Tinjauan Sistematis Studi Kohort - Utami, Fista; Rusydiana, Hamidah Aula; Dini, Cleonara Yanuar; Bertalina; Wahyuni, Endang Sri (Universitas Airlangga, 2026)
Background: The nutritional management of CKD has traditionally focused on total protein intake. While animal proteins provide high bioavailability, their acid load production may contribute to CKD. Plant proteins serve as alternative sources due to their protective properties. Thus, the optimal plant-to-animal protein ratio is essential for developing dietary strategies that balance nutritional requirements with long-term renal preservation. Objectives: This review aimed to synthesize current evidence on the association between plant protein intake and kidney-related outcomes across different populations and CKD stages. Methods: Cohort studies were included, investigating adult populations with or without CKD. Exposure variables comprise plant protein intake or the proportion of plant-to-total protein, compared with lower plant protein or higher animal protein consumption. Outcomes assessed included eGFR, CKD incidence, and all-cause mortality. Literature searches used predefined keywords related to protein sources and kidney outcomes. Data were extracted and narratively synthesized following the Joanna Briggs Institute (JBI) guidelines. Results: Seven studies conducted between 2016 and 2025 across China, Iran, the United States, Australia, and the United Kingdom were included. Higher intake of plant protein was consistently associated with better kidney outcomes, including higher eGFR, slower decline in kidney function, reduced CKD, and lower mortality risk among individuals with impaired kidney function. Additionally, plant protein intake may mitigate the negative impact of sedentary behavior on CKD risk. Conclusions: Plant proteins play a protective role in kidney health. Incorporating plant-based protein into a healthy lifestyle may be a modifiable strategy for preventing and managing CKD.